Implementasi Metode Demonstrasi Pada Materi Sholat dan Dzikir Kelas VII A di SMP N 3 Sragi Kabupaten Pekalongan - Fatmasari, Shinta; Hanani, Cici; Dwi Aprilia, Dita; Fika Mulia, Rizky; Satrio Wibowo, Alvin (Darajat: Jurnal Pendidikan Agama Islam, 2023)
The purpose of teaching and learning activities is to influence student behavior. The change in question is how one shows up in terms of one's mental, social, and skills. Methods are required in learning to achieve this modification. So that students can witness the growth of their critical thinking skills. From ignorant to knowledgeable, able to distinguish between right and wrong, and experiencing positive behavioral changes. In carrying out learning, methods are needed to achieve these changes. The demonstration method is an instructional approach in which props that have previously been given an explanation of how to use them are practiced, demonstrated, or demonstrated. Because the learning material in PAI learning is routine and involves movement, demonstration techniques will be well applied in practice-based learning, such as elements of fiqh material. Given that prayer and dhikr are components of the foundation of fiqh, chapters on these two topics will be discussed demonstratively in this regard. Observation, documentation, and interviews are the methods used in this qualitative research to gather data sources.